Developing a Framework for Establishing Clinical Decision Support Meaningful Use Objectives for Clinical Specialties - Damberg, Cheryl L. (RAND Corporation, 2012)
The federal electronic health record (EHR) incentive program includes clinical decision support (CDS) as a central requirement of improving health outcomes; however, a process for identifying and prioritizing the most promising targets for CDS has not been established. This report describes a protocol for eliciting high-priority targets for electronic CDS for individual clinical specialties and summarizes lessons learned.